A prospective study to evaluate the role of serum vascular endothelial growth factor levels and color Doppler indices in prediction of malignancy in adnexal masses - Tahmina, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Several markers have been used for predicting malignancy in adnexal masses. Objectives were to measure preoperative serum vascular endothelial growth factor (VEGF) and to determine its value in predicting risk of malignancy in adnexal masses, in combination with colour Doppler indices (resistance index, RI; pulsatility index, PI). Methods: A hospital based prospective observational study was conducted in 79 women with 102 adnexal masses, who underwent a preoperative colour doppler ultrasound and CA-125 and VEGF levels were estimated. Cut-off levels for suspicion of malignancy were taken at CA-125>35IU/ml, RI<0.56, PI<1.0. Study variables were correlated with the histopathological diagnosis and their sensitivity, specificity, predictive values and accuracy for detecting malignancy were computed. Receiver operating characteristic (ROC) curve analysis was performed to assess serum VEGF and Doppler indices as markers for detection of malignant masses. Results: Among 96 adnexal masses studied, ten (10.4%) were malignant, 33 (34.4%) benign, one (1%) borderline and remaining were non-neoplastic. RI and PI accurately predicted malignancy in 93.75% and 88.54% cases respectively, while CA-125 was 64.58% accurate. The mean VEGF level in malignant was significantly higher than that in benign cases (1761±1381.7pg/ml, 429.8±501.9 pg/ml respectively, p-value < 0.001). Combination of VEGF, RI and PI was 96% accurate in detecting malignancy in adnexal masses. Conclusions: Serum VEGF may be a useful marker to screen for malignancy in an adnexal mass, at a cut-off of ≥1080pg/ml. Addition of RI and PI to VEGF increased the specificity and diagnostic accuracy, performing better than CA-125, RI and PI, when used independently or together.